Peran Research Marketing Terhadap Database Perusahaan di PT. Petik Emas Consulting - Sheren Olivia Cendrawan; Arton Briyan Prasetio; Stella Stella; Wibisono Soediono (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This internship report is intended to explain the author's activities in the internship process with PT. Petik Emas Consulting through Magang Bersertifikat Kampus Merdeka program. This report will explain how the author's daily life as part of Marketing Intern. The things described will include the author's activities in searching for data, information, and facts related to research (competitors, companies, social enterprises, and social innovation) through the internet and interviews. The form of output from market research activities carried out will be collected into a social innovation outlook.